The relevance of Al-Farabi’s classification of knowledge in the modern higher educational institution: the case of Malaysia - Watib, Nur Hafizah; Awang Mat , Muhamad Zahiri; Endut@Abdul Razak, Nadia; Abdul Razak, Nuriah; Marusin, Ratinah (Association of Malaysian Muslim Intellectuals, 2013)
Al-Farabi is a great Muslim scholar who had contributed to the development of knowledge. This can be seen from his work on ‘Enumeration of science’, where he classified knowledge into several divisions. This study employed an analytical approach in analyzing his writing of the ‘Enumeration of the Sciences’ as well as to compare, contrast and to conclude its relevance and implication towards the selected current higher educational institutions in Malaysia. It is found that first, al-Farabi classified knowledge based on philosophical approach. Second, his classification suits the need of the higher educational institution in Malaysia.